Fast retransmission mechanism and end to end QoS support for VoIP applications over IEEE 802.11e WLANs - Tüysüz, Mehmet Fatih; Mantar, Haci Ali (My University, 2011)
Real-time applications such as VoIP, video-conference or online games are delay-sensitive multimedia applications and require relatively small delay and small delay variation. Recently, IEEE 802.11 WLANs have reached an important stage and have become a common technology for wireless access due to its low cost, ease of deployment and mobility support. Its new standard, EDCA, has the ability to accommodate real-time traffic and provide relatively small delay. However, it cannot achieve small delay variation due to the burst feature of its backoff mechanism after a collision or a frame error. Since the real-time services such as Voice over IP (VoIP) has a delay constraint to guarantee a QoS, a fast retransmission scheme for corrupted frames is required. In this paper, we propose a new fast retransmission mechanism for VoIP frames to reduce the delay and delay variation. Then, we integrate our scheme with an Adaptive Jitter Buffer (AJB) algorithm to optimize end-to-end QoS performance. Simulation results indicate that proposed fast retransmission scheme reduces not only delay, delay variation and dropping probability of frames, but it also helps the AJB to support QoS maintaining voice quality at high level on EDCA-based WLANs. © 2011 IEEE. © 2012 Elsevier B.V., All rights reserved.
2011 International Conference on Information Technology and Multimedia: "Ubiquitous ICT for Sustainable and Green Living", ICIM 2011 -- Kajang -- 88267
Keywords: Adaptive jitter buffer; Energy bursts; QoS; Retransmission; Voice over ip (VoIP); Wireless networks